Fluoride-based hydrogen bond chemistry in a layered double hydroxide cathode toward high-performance aqueous NH 4 + storage - Fang-Fang Sun; Xinwei Guan; Zi-Hang Huang; Xu Han; Hui Li; Tianyi Ma (Proceedings of the National Academy of Sciences, 2025)
In aqueous ammonium-ion storage, hydrogen bonds play a pivotal role in the reversible insertion/extraction of NH 4 + within transition metal oxides/hydroxides. Although fluorine (F) is known for its strong electronegativity and potential to form robust hydrogen bonds with NH 4 + , its specific influence on NH 4 + storage remains unexplored. Herein, we systematically investigate the effects of F-based hydrogen bond chemistry within a layered double hydroxide matrix, where F species are introduced and subsequently partially removed via an electrochemical method. Our findings demonstrate that while increasing F doping content accelerates NH 4 + diffusion due to F’s strong electronegativity, it also triggers crystal shrinkage and depresses storage capacity. To this end, controlled partial removal of F, employing a lye-assistant electrochemical strategy, induces expanded interlayer spacing and distinct edge lattice tearing, thereby facilitating improved NH 4 + accommodation. The retained F sites couple with emerging exposed O sites maintain a high hydrogen bonding capability, which is further enhanced by the formation of highly active, curved hydroxyl groups centered around F sites. These manipulations significantly boost the NH 4 + storage performance of the electrode, providing insights into leveraging the strongest F-based hydrogen bond chemistry in developing high-performance ammonium-ion energy storage devices.